P‐FLUX: A phosphorus budget dataset spanning diverse agricultural production systems in the United States and Canada. Issue 3 (25th April 2022) - Williams, M. R.; Welikhe, P.; Bos, J.; King, K.; Akland, M.; Augustine, D.; Baffaut, C.; Beck, E.G.; Bierer, A.; Bosch, D.D.; Boughton, E.; Brandani, C.; et al.
Abstract: Quantifying spatial and temporal fluxes of phosphorus (P) within and among agricultural production systems is critical for sustaining agricultural production while minimizing environmental impacts. To better understand P fluxes in agricultural landscapes, P‐FLUX, a detailed and harmonized dataset of P inputs, outputs, and budgets, as well as estimated uncertainties for each P flux and budget, was developed. Data were collected from 24 research sites and 61 production systems through the Long‐term Agroecosystem Research (LTAR) network and partner organizations spanning 22 U.S. states and 2 Canadian provinces. The objectives of this paper are to (a) present and provide a description of the P‐FLUX dataset, (b) provide summary analyses of the agricultural production systems included in the dataset and the variability in P inputs and outputs across systems, and (c) provide details for accessing the dataset, dataset limitations, and an example of future use. P‐FLUX includes information on select site characteristics (area, soil series), crop rotation, P inputs (P application rate, source, timing, placement, P in irrigation water, atmospheric deposition), P outputs (crop removal, hydrologic losses), P budgets (agronomic budget, overall budget), uncertainties associated with each flux and budget, and data sources. Phosphorus fluxes and budgets vary across agricultural production systems and are useful resources to improve P use efficiency and develop management strategies to mitigate environmental impacts of agricultural systems. P‐FLUX is available for download through the USDA Ag Data Commons (https://doi.org/10.15482/USDA.ADC/1523365 ). Core Ideas: Assessing P fluxes and budgets is critical for sustainable agricultural intensification. P fluxes and budgets were determined for 61 production systems in the USA and Canada. P inputs, outputs, and budgets were highly variable across production systems. A detailed and harmonized dataset of P fluxes/budgets and uncertainties was developed. Data are available as comma‐separated (.csv) files through the USDA Ag Data Commons.